Microstructure and mechanical properties of aluminium matrix boron carbide and carbon nanofiber reinforced hybrid composites - Okay Faik; Islak Serkan (National Library of Serbia, 2022)
In this study, aluminium matrix boron carbide (B4C) and carbon nanofiber (CNF) reinforced hybrid composite was produced by powder metallurgy method and their microstructure and mechanical properties were investigated. The samples were produced at 6 percentage volume ratios using hot pressing technique. Microstructure examination, hardness measurement, transverse rupture test, and wear tests were carried out in order to determine the mechanical properties of the samples. Also three-point bending test was performed to determine their transverse rupture strength (TRS). Wear tests were carried out based on the ball on disc method. The microstructure examination revealed that the reinforcing elements were relatively homogeneously distributed in the aluminium matrix. In addition, the fracture was brittle due to the notch effect and agglomeration occurred with increasing amount of CNF. As the CNF amount of the samples increased, their hardness values increased but their TRS values decreased. Results of the wear test indicate that the increased amount of CNF increased the wear resistance. The friction coefficient values of the samples varied between 0.535 and 0.646. When the hardness was examined together with TRS and wear test results, the most suitable sample was determined to be Al-7%B4C-1%CNF
Keywords: wear; Chemical technology; microstructure; cnf; trs; TP1-1185; hybrid composites